Nitrogen fertilization and glyphosate‐resistant alfalfa termination method effects on first‐year silage corn. (10th March 2021) - Clark, Jason D.; Yost, Matt A.; Griggs, Thomas C.; Cardon, Grant E.; Ransom, Corey V.; Creech, J. Earl
Abstract: Tillage type/timing and herbicide application date may change the amount and timing of N mineralization, altering fertilizer N needs for first‐year corn ( Zea mays L.) following glyphosate [N‐(phosphonomethyl)glycine]‐resistant (GR) alfalfa ( Medicago sativa L.). Studies were conducted in 2012 and 2013 in Utah. Yield, quality, and economic return of silage corn as affected by five tillage type/timings (fall conventional till, spring conventional till, fall strip‐till, spring strip‐till, and no‐till), three herbicide application dates for alfalfa termination (fall, spring, and in‐crop), and four N rates (0, 56, 112, and 224 kg ha −1 ) were evaluated. Silage corn yield and quality following GR alfalfa was economically optimized without N fertilization regardless of tillage type/timing and herbicide application date. Thus, N from decomposing alfalfa can provide the full N requirement of first‐year silage corn following GR alfalfa. Estimated animal milk production ha −1 of silage corn was greatest and similar for all herbicide application dates with conventional tillage and spring herbicide application with strip‐till and no‐till (26–38 Mg milk ha −1 ), whereas an in‐crop herbicide application with strip‐till and no‐till resulted in the lowest estimated milk production (21–29 Mg milk ha −1 ). Increased economic return for the in‐crop herbicide date by including economics from harvesting the first alfalfa cutting before planting corn mostly offset the reduced economic return of the lower silage corn yield. Therefore, an application of 2, 4‐D (2, 4‐dichlorophenoxyacetic acid) and dicamba (3, 6‐dichloro‐2‐methoxybenzoic acid) in the fall, spring, or in‐crop to control GR alfalfa are good economic options for conventional tillage, strip‐till, and no‐till systems. Core Ideas: Decomposition of alfalfa provided full N requirement of silage corn regardless of tillage system. Terminating glyphosate‐resistant alfalfa in the spring optimized silage corn quality with strip‐till and no‐till. Silage corn quality was similar with conventional tillage regardless of herbicide application date. Terminating alfalfa after corn emergence reduced estimated milk production from silage corn. Profit was similar for all herbicide timings when including revenue from corn and alfalfa.